Pengaruh Beban Dan Kepuasan Kerja Terhadap Kinerja Karyawan Dengan Metode Structural Equation Modeling (SEM) Di PT. Indonesia Tri Sembilan - Dzulfikar Al-Muhtadi; Sumiati Sumiati (Jurnal Penelitian Rumpun Ilmu Teknik, 2023)
One concern to support the success of the company is about the performance of each employee. Employee performance has several factors that can influence it, including satisfaction and workload received by each employee in the company. PT. Indonesia Tri Sembilan feels that the performance of its employees is still not optimal and it is felt that it can be improved further, therefore an evaluation is needed on the factors that affect the level of employee performance. The variables used are performance, job satisfaction, and employee workload. Data collection used the questionnaire distribution method and data processing used the IBM SPSS Statistics 26 and SmartPLS 4 applications. Respondents are permanent staff at PT. Indonesia Tri Sembilan with a total of 39 people. From the results of the research, the researchers stated that there was a significant influence between Job Satisfaction and Performance and had a positive effect. Researchers also stated that there was a significant influence between workload and performance but had a negative effect.